G65V Substitution in Actin Disturbs Polymerization Leading to Inhibited Cell Elongation in Cotton - Sun, Yongwang; Liang, Wenhua; Shen, Weijuan; Feng, Hao; Chen, Jiedan; Si, Zhanfeng; Hu, Yan; Zhang, Tianzhen (Frontiers in Plant Science, 2019)
The importance of the actin cytoskeleton for proper cell development has been well established in a variety of organisms. Actin protein sequences are highly conserved, and each amino acid residue may be essential for its function. In this study, we report the isolation and characterization of GhLi1 from an upland cotton mutant Ligon lintless-1 (Li1), which harbors the G65V substitution in its encoded actin protein. Li1 mutants exhibit pleiotropic malformed phenotypes, including dwarf plants, distorted organs, and extremely shortened fibers. Cytological analysis showed that the actin cytoskeleton was disorganized and the abundance of F-actin was decreased in the Li1 cells. Vesicles were aggregated into patches, and excessive cellulose synthase complexes were inserted into the plasma membrane during the secondary cell wall biosynthesis stage, which dramatically affected the morphology of the Li1 cells. Molecular model prediction suggested that the G65V substitution may affect the three-bodied G-actin interaction during F-actin assembly. Biochemical assays demonstrated that the recombinant GhLi1 protein disturbs actin dynamics by inhibiting the nucleation and elongation processes. Therefore, our findings demonstrate that the G65V substitution in actin had dominant-negative effects on cell elongation, by disturbing actin polymerization and actin cytoskeleton-based biological processes such as intracellular transportation.